Pengaruh Produk Domestik Bruto, Nilai Tukar Rupiah dan Harga Minyak Dunia terhadap Neraca Perdagangan - Lisa Fadilla Sitorus; Bima Hardi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine the effect of gross domestic product, the rupiah exchange rate, and world oil prices on the trade balance partially and simultaneously. The method used is associative quantitative research with the Error Correction Model (ECM). The results of the study state that in the short term, gross domestic product and world oil prices do not affect the trade balance, but the rupiah exchange rate does. In the long term, GDP and world oil prices affect the trade balance, but the rupiah exchange rate does not. Simultaneously, in the short term, the F-count value < t-table (1.971849 < 2.048) with a probability value of 0.128531 > 0.05. And in the long term, the F-count value > t-table (21..71070 > 2.048) with a probability value of 0.000000 < 0.05, the long-term Adjusted R-square value is 0.769 (76%) meaning that 76% of the models in the study can explain the trade balance. and the rest is influenced by other variables outside the model.